2009
DOI: 10.1007/s00253-009-1904-0
|View full text |Cite
|
Sign up to set email alerts
|

Export of functional Streptomyces coelicolor alditol oxidase to the periplasm or cell surface of Escherichia coli and its application in whole-cell biocatalysis

Abstract: Streptomyces coelicolor A3(2) alditol oxidase (AldO) is a soluble monomeric flavoprotein in which the flavin cofactor is covalently linked to the polypeptide chain. AldO displays high reactivity towards different polyols such as xylitol and sorbitol. These characteristics make AldO industrially relevant, but full biotechnological exploitation of this enzyme is at present restricted by laborious and costly purification steps. To eliminate the need for enzyme purification, this study describes a wholecell AldO b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 45 publications
4
17
1
Order By: Relevance
“…This revealed that the removal of LPS (components of the cell membrane) did help to reduce the steric hindrances and enhance the outer-membrane protein expression. This result is consistent with that suggested by Bloois et al that the surface display of alditol oxidase might be restricted by LPS in the wild-type E. coli host [31]. Strain JM109 (lon mutation) was observed to give the highest EGFP production.…”
Section: Host Effectssupporting
confidence: 94%
“…This revealed that the removal of LPS (components of the cell membrane) did help to reduce the steric hindrances and enhance the outer-membrane protein expression. This result is consistent with that suggested by Bloois et al that the surface display of alditol oxidase might be restricted by LPS in the wild-type E. coli host [31]. Strain JM109 (lon mutation) was observed to give the highest EGFP production.…”
Section: Host Effectssupporting
confidence: 94%
“…However, the ratio of cell lysate activity to wholecell activity for the periplasmic CA system was an order of magnitude lower (ϳ6) than that of the cytoplasmic CA system (ϳ102). This observation clearly indicates the effectiveness of periplasmic translocation for overcoming the physical or physiological barriers imposed by the cytoplasmic membrane (22,39). Again, this indirectly demonstrated that ngCA was successfully exported into the periplasm of E. coli.…”
Section: Resultsmentioning
confidence: 53%
“…In summary, the choice of export pathway is dictated by the properties of the target protein. This is exemplified by our study on exporting AldO, a flavoprotein oxidase, to the periplasm of E. coli [15]. AldO contains covalently bound FAD, which will only form upon linkage to polypeptide chain.…”
Section: Introductionmentioning
confidence: 94%
“…The latter is well illustrated by our finding that cells which express AldO in the cytoplasm are unable to convert xylitol. In contrast, xylitol was readily converted by cells that export AldO Tat-dependently to the periplasm [15]. Next, we constructed a xylitol biosensor comprising AldO equipped with a microperoxidase (MP) domain.…”
Section: Whole-cell Biocatalysismentioning
confidence: 99%